The right planum temporale is involved in stimulus-driven, auditory attention--evidence from transcranial magnetic stimulation. - Marco Hirnstein (Public Library of Science (PLoS), 2013)
It is well known that the planum temporale (PT) area in the posterior temporal lobe carries out spectro-temporal analysis of auditory stimuli, which is crucial for speech, for example. There are suggestions that the PT is also involved in auditory attention, specifically in the discrimination and selection of stimuli from the left and right ear. However, direct evidence is missing so far. To examine the role of the PT in auditory attention we asked fourteen participants to complete the Bergen Dichotic Listening Test. In this test two different consonant-vowel syllables (e.g., "ba" and "da") are presented simultaneously, one to each ear, and participants are asked to verbally report the syllable they heard best or most clearly. Thus attentional selection of a syllable is stimulus-driven. Each participant completed the test three times: after their left and right PT (located with anatomical brain scans) had been stimulated with repetitive transcranial magnetic stimulation (rTMS), which transiently interferes with normal brain functioning in the stimulated sites, and after sham stimulation, where participants were led to believe they had been stimulated but no rTMS was applied (control). After sham stimulation the typical right ear advantage emerged, that is, participants reported relatively more right than left ear syllables, reflecting a left-hemispheric dominance for language. rTMS over the right but not left PT significantly reduced the right ear advantage. This was the result of participants reporting more left and fewer right ear syllables after right PT stimulation, suggesting there was a leftward shift in stimulus selection. Taken together, our findings point to a new function of the PT in addition to auditory perception: particularly the right PT is involved in stimulus selection and (stimulus-driven), auditory attention.